The law of collaborative defence procurement through international organisations in the European Union - Heuninckx, Baudouin (2011)
This thesis critically analyses the procurement rules of international organisations or agencies performing collaborative defence procurement in the European Union (EU). In collaborative defence procurement, States agree to procure equipment or services for their armed forces in common, thereby sharing development costs and looking for economies of scale. The management of collaborative defence procurement programmes is often entrusted to an international organisation or agency acting on behalf of the participating States. After setting out the political, economic and legal context of collaborative defence procurement in the EU, we analyse the applicability of domestic and EU law to international organisations, in particular public procurement law in the field of defence. The conclusion of this first part is that, whilst domestic and EU law apply in general terms to international organisations or agencies, this is subject to the substantive provisions of the relevant laws and to international law, such as the privileges and immunities of the organisations. Specifically, international organisations or agencies in the EU most likely would not have to comply with domestic procurement law or with the EU public procurement directives, but they would still have to comply with the procurement principles flowing from the EU Treaties, except if non-EU Member States control their decision-making. We then move on to an analysis of the procurement rules of three international organisations or agencies performing collaborative defence procurement in the EU: the Joint Organisation for Armaments Cooperation (OCCAR), the NATO Maintenance and Supply Organisation (NAMSO) and the European Defence Agency (EDA). For these organisations we analyse to what extent their procurement rules should comply with EU law, to what extent they are an efficient set of rules, and what measures could be taken to remedy any detrimental issue or incoherence identified. We conclude with recommendations aiming to improve the applicable law.